Mothers' teething beliefs and treatment practices in Mansoura, Egypt - Abdel-H; Fawzia El Sayed Abusaad (Elsevier, 2017)
Objectives: To reveal mothers' beliefs about signs and symptoms associated with teething and their treatment practices. Population and methods: A cross-sectional study done in Mansoura District on 457 mothers and their children with one or more erupted teeth. Mothers were interviewed during vaccination session at 25 chosen health facilities. Mothers were asked whether they agree or disagree about 24 signs and symptoms claimed to be associated with teething. Results: Only 1.8% reported no symptoms at the time of teething. Majority had correct knowledge related to bite fingers/objects (70.5%) and drooling (60.0%). Inaccurate knowledge was reported as gum rubbing (42.0%), gum swelling (47.0%), diarrhea (51.0%), fever (83.2%) and weight loss (46.0%). Only 16.8% of mothers have good knowledge about teething problems. Logistic regression analysis revealed that the independent predictors of good knowledge are higher education (AOR = 3.7), urban residence (AOR = 2.5) and having a first-born child (AOR = 5.5). Only 13.4% of mothers did not give any treatment for teething problems. Antipyretics and antibiotics were the most frequently given treatments (71.3%, and 24.3%; respectively). Conclusions: The majorities of mothers had low knowledge about teething problems and gave unnecessary treatments. Keywords: Teething, Teething signs, Teething symptoms, Misconception, Mothers' knowledge, Egypt